Accurate staging of non-small cell lung cancer—tissue is the issue - Navani, Neal (Journal of Thoracic Disease, 2019)
I thank the journal for the interest in our article (1) and Dr. Jantz for his thoughtful comments. I agree with Dr. Jantz’s stance on the importance of mediastinal staging for non-small cell lung cancer (NSCLC) and agree that data from investigations for lung cancer staging are established.